Analisis Kualitas Fisik Hand sanitizer Ekstrak Serai dan Cengkeh Serta Kemampuannya dalam Menghambat Pertumbuhan Staphylococcus aureus - Diana Sari; Abdul Karim; Faisal Amri Tanjung; Riyanto Riyanto (Universitas Medan Area, 2023)
Hand sanitizer is an antiseptic substance that can be used to clean hands. To reduce the chemical content in Hand sanitizers, by using natural ingredients that contain antimicrobial ingredients. The natural ingredients used in this study were lemongrass and cloves. The purpose of this study was to determine the physical quality (organoleptic, homogeneity), phytochemical content and effectiveness of lemongrass and clove extracts against Staphylococcus aureus bacteria. This study uses an experimental laboratory research method where the data obtained in the observations are presented in the form of quantitative descriptive analysis with concentrations of 0%, 25%, 50%, 75%, 100% in 5 days, 7 days and 10 days of fermentation. The results of the organoleptic test got the results of color, shape and liquid texture, the results of the homogeneity test were that there were still coarse grains on the Hand sanitizer. The results of the phytochemical content of lemongrass and clove extracts are flavonoids and tannins. The results of the effectiveness test showed that lemongrass and clove extracts were able to inhibit Stahpylococcus aureus bacteria in 5 days, 7 days and 10 days of fermentation. The largest inhibition zone was found in the 7-day fermentation with 100% concentration of 0.86 mm.